Alicanto czy simurg? O zmianie orientacji na innowacje i przywództwo w szkolnej codzienności = Alicanto or simurgh? On the re-orientation towards innovation and leadership in everyday school life - Nowosad, Inetta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The incorporation of Simurgh and Alicanto metaphors in the title is meant to draw attention to two opposite types of leadership and to refine the understanding of the approach to innovation that has been practiced at school. In the pursuit of such a specific objective, the author analyzed selected theoretical approaches and studies on effective models of leadership, i.e., models that ensure a sustainable development of the school community. The adoption of the organizational learning theory exposes the orientation towards change and school transformation towards improvement.
Keywords: kultura szkoły; przywództwo laissez-faire; przywództwo transakcyjne; przywództwo transformacyjne; rozwój szkoły; innovation; laissez-faire leadership; transactional leadership; transformational leadership; school development